Positive electrode material precursor, single crystal positive electrode material and preparation method, lithium ion battery
The single crystal positive electrode material prepared through atomization treatment and high-temperature sintering solves the problem that traditional materials are prone to microcracks during charging and discharging, and achieves lower DC internal resistance and improved magnification and cycling performance.
Patent Information
- Application Number
- CN202311331910.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-10-13
AI Technical Summary
The existing single-crystal ternary positive electrode materials are prone to crystal surface slippage, dislocation and other phenomena during charging and discharging, resulting in the occurrence of microcracks and reducing the material's cycling and rate performance.
By atomizing the mixed solution containing nickel salt, cobalt salt and manganese salt and thermally decompose it, a positive electrode material precursor was obtained, and mixed with a lithium source and sintered under an oxygen atmosphere to prepare a single crystal positive electrode material with low lattice strain. The Ni, Co and Mn elements of this material are uniformly distributed, reducing crystal structure defects and lattice stress.
It achieves a low DC internal resistance (DCR) of single crystal positive electrode material, improves rate performance and cycling performance, and extends the service life of the material.
Smart Images

Figure CN117457890B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a positive electrode material precursor, a single crystal positive electrode material and a preparation method, and a lithium ion battery. Background Art
[0002] Lithium-ion cathode materials are mainly divided into lithium iron phosphate and ternary materials. Lithium iron phosphate is superior to ternary materials in cost, cycle life and thermal stability, and is suitable for commercial vehicles, low-end and mid-range passenger cars, energy storage and other fields. Ternary materials have high energy density and good low-temperature performance, and are suitable for mid-end and high-end passenger cars.
[0003] During the charge and discharge process, traditional polycrystalline ternary positive electrode materials are prone to local stress along the grain boundaries as the lattice shrinks, causing the material structure to collapse, forming microcracks, and causing the positive electrode material capacity to decay rapidly. Single crystalization is a way to improve the cycle performance of ternary materials. Single crystal ternary materials eliminate grain boundaries, can inhibit the cracking of positive electrode materials during the charge and discharge process, and show excellent stability. However, single crystal ternary materials also face other problems. The diffusion path of Li in single crystal ternary materials is long, resulting in slow Li transmission power, and the performance is manifested as large DC internal resistance (DCR) and poor rate performance. In addition, although single crystal particles can inhibit particle cracking, crystal plane slip, dislocation and other phenomena will still occur during the cycle, further generating microcracks.
[0004] Ternary single crystal cathode materials are generally prepared by high-temperature sintering of Ni / Co / Mn-containing precursor compounds and lithium salts. During the sintering process, the formation of cathode materials is usually very slow, and the growth rate is uneven, resulting in stress concentration inside the cathode materials formed; in addition, due to the limitation of ion diffusion, there are concentration differences in the distribution of elements in the ternary materials, resulting in mismatched lattice parameters inside the materials. On the one hand, this will hinder the transmission of lithium ions, thereby increasing the impedance of the cathode materials and reducing the rate performance of the cathode materials; on the other hand, the internal lattice micro-stress makes the cathode materials prone to cracking and pulverization during the cycle, reducing the cycle performance of the cathode materials.
[0005] Therefore, how to improve the rate performance of single crystal positive electrode materials, reduce impedance, and further improve cycle performance are technical problems that still need to be solved. Summary of the invention
[0006] The purpose of the present application is to provide a positive electrode material precursor, a single crystal positive electrode material and a preparation method, and a lithium ion battery. The single crystal positive electrode material provided by the present application has low lattice strain, which can reduce the diffusion energy barrier of lithium ions between microcrystals and improve the Li ion diffusion coefficient, so that the single crystal positive electrode material exhibits a lower DCR and the single crystal positive electrode material has good rate performance; it can also reduce the occurrence of crystal plane slip, dislocation and the like, thereby inhibiting the generation of microcracks, improving the structural stability of the single crystal positive electrode material, and thereby improving the cycle performance of the single crystal positive electrode material.
[0007] In a first aspect, the present invention provides a single crystal positive electrode material, wherein the chemical formula of the single crystal positive electrode material is Li x Ni a Co b Mn c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y;
[0008] When observing the single crystal positive electrode material with a scanning electron microscope, at a magnification of 3K, 10 points of the single crystal positive electrode material are randomly selected for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the single crystal positive electrode material, the standard deviation of the mass content of each element of Ni, Co, and Mn in the single crystal positive electrode material is ≤0.03;
[0009] The lattice strain of the single crystal positive electrode material is ε, and ε is less than 0.2%.
[0010] In some embodiments, the grain size of the single crystal positive electrode material is D, 150nm<D<250nm.
[0011] In some embodiments, the average particle size D of the single crystal positive electrode material is 50 It is 1.5μm~5μm.
[0012] In some embodiments, the tap density of the single crystal positive electrode material is greater than 1.5 g / cm 3 .
[0013] In some embodiments, the range of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.08.
[0014] In a second aspect, the present invention provides a positive electrode material precursor, the chemical formula of which is Ni a Cob Mn c N d O e , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y;
[0015] The surface area weighted average particle size D[3, 2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is less than or equal to 0.05.
[0016] In some embodiments, the range of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.12.
[0017] In some embodiments, the cathode material precursor includes secondary particles, and the secondary particles include a plurality of agglomerated primary particles.
[0018] In some embodiments, the cathode material precursor includes secondary particles, the secondary particles include a plurality of agglomerated primary particles, and the primary particles are spherical.
[0019] In some embodiments, the cathode material precursor includes secondary particles, the secondary particles include a plurality of agglomerated primary particles, and the particle size of the primary particles is 20 nm to 1000 nm.
[0020] In some embodiments, the average particle size D of the positive electrode material precursor is 50 <3.5μm.
[0021] In some embodiments, the specific surface area of the cathode material precursor is greater than 5 m 2 / g.
[0022] In some embodiments, the tap density of the cathode material precursor is greater than 1 g / cm 3 .
[0023] In a third aspect, the present application provides a method for preparing a single crystal positive electrode material, comprising the following steps:
[0024] A mixed solution containing nickel salt, cobalt salt and manganese salt is atomized and then thermally decomposed to obtain a positive electrode material precursor, wherein the surface area weighted average particle size D[3,2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.05;
[0025] The positive electrode material precursor is mixed with a lithium source and sintered in an oxygen-containing atmosphere to obtain a single crystal positive electrode material, wherein the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.03; and the lattice strain of the single crystal positive electrode material is ε, and ε<0.2%.
[0026] In some embodiments, the nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate.
[0027] In some embodiments, the cobalt salt includes at least one of cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt sulfate, cobalt nitrate, and cobalt acetate.
[0028] In some embodiments, the manganese salt includes at least one of manganese chloride, manganese carbonate, manganese sulfate, manganese oxalate, manganese nitrate, and manganese acetate.
[0029] In some embodiments, the molar ratio of Ni, Co and Mn in the mixed solution is (50-98):(0-20):(0-30), and the content of Co and Mn in the mixed solution is not zero.
[0030] In some embodiments, the total metal concentration in the mixed solution is 200 g / L to 500 g / L.
[0031] In some embodiments, the mixed solution further includes a dopant containing an N element, wherein N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn, and Y.
[0032] In some embodiments, the chemical formula of the cathode material precursor is Ni a Co b Mn c N d O e , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
[0033] In some embodiments, the range of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.12.
[0034] In some embodiments, the flow rate of the mixed solution is 100 L / h to 900 L / h.
[0035] In some embodiments, the pressure of the atomization treatment is 0.4 MPa to 0.8 MPa.
[0036] In some embodiments, the primary sintering temperature is 500°C to 850°C.
[0037] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.
[0038] In some embodiments, the molar ratio of lithium in the lithium source to the sum of nickel, cobalt and manganese in the positive electrode material precursor is 0.98 to 1.10.
[0039] In some embodiments, the sintering temperature is 750°C to 950°C.
[0040] In some embodiments, the sintering time is 10 h to 30 h.
[0041] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the single crystal positive electrode material described in the first aspect or the single crystal positive electrode material prepared by the method for preparing the single crystal positive electrode material described in the third aspect.
[0042] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:
[0043] The single crystal positive electrode material provided in the present application randomly selects 10 points of the single crystal positive electrode material for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the single crystal positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.03, indicating that the distribution uniformity of Ni, Co, and Mn elements inside the single crystal positive electrode material is good, which is conducive to reducing the crystal structure defects of the single crystal positive electrode material; the lattice strain ε of the single crystal positive electrode material is less than 0.2%, which can reduce the diffusion energy barrier of lithium ions between crystallites and increase the Li ion diffusion coefficient, so that the single crystal positive electrode material exhibits good rate performance and low DCR; at the same time, low lattice strain can also inhibit the generation of microcracks in the single crystal positive electrode material, thereby improving the cycle performance of the single crystal positive electrode material.
[0044] The positive electrode material precursor provided by the present application has a surface area weighted average particle size D[3, 2]<2.0μm, has high reaction activity, and is beneficial to improving the reaction efficiency and mass transfer efficiency in the subsequent preparation process of the positive electrode material from the positive electrode material precursor; at the same time, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor obtained by the above preparation method is ≤0.05, indicating that the distribution uniformity of Ni, Co and Mn elements in the positive electrode material precursor is good; using the positive electrode material precursor to prepare the positive electrode material can improve the distribution uniformity of Ni, Co and Mn elements in the positive electrode material, so that the positive electrode material prepared by the positive electrode material precursor has fewer crystal structure defects and smaller lattice stress.
[0045] The single crystal positive electrode material preparation method provided in the present application is to obtain a positive electrode material precursor by atomizing a mixed solution containing nickel salt, cobalt salt and manganese salt and then thermally decomposing it. The surface area weighted average particle size D[3,2] of the positive electrode material precursor is less than 2.0 μm, and the reaction activity is high, which is beneficial to improve the reaction efficiency and mass transfer efficiency of the positive electrode material precursor and the lithium source in the subsequent high-temperature sintering process; at the same time, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor obtained by the above preparation method is ≤0.05, indicating that the distribution uniformity of Ni, Co and Mn in the positive electrode material precursor is good; and then the single crystal positive electrode material prepared by the above positive electrode material precursor after subsequent sintering with the lithium source is The standard deviation of the mass content of the elements is ≤0.03, and the distribution uniformity of Ni, Co, and Mn elements inside the single crystal positive electrode material is good, which is conducive to reducing the crystal structure defects of the single crystal positive electrode material; and the lattice strain of the single crystal positive electrode material is low, and its lattice strain ε is less than 0.2%, which can reduce the diffusion energy barrier of lithium ions between crystallites and improve the Li ion diffusion coefficient, so that the single crystal positive electrode material exhibits good rate performance and low DCR; at the same time, low lattice strain can also inhibit the generation of microcracks in the single crystal positive electrode material, thereby improving the cycle performance of the single crystal positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0047] Figure 1 This is a SEM morphology image of the positive electrode material precursor prepared in Example 1 of the present application;
[0048] Figure 2 Another SEM morphology image of the cathode material precursor prepared in Example 1 of the present application;
[0049] Figure 3 This is the EDS spectrum result of the positive electrode material precursor prepared in Example 1 of the present application;
[0050] Figure 4This is the Williamsone-Hall analysis fitting curve of the single crystal positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0051] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0052] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0054] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0055] In a first aspect, the present invention provides a single crystal positive electrode material, wherein the chemical formula of the single crystal positive electrode material is Li x Ni a Co b Mn c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y;
[0056] When observing the single crystal positive electrode material with a scanning electron microscope, at a magnification of 3K, 10 points of the single crystal positive electrode material are randomly selected for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the single crystal positive electrode material, the standard deviation of the mass content of each element of Ni, Co, and Mn in the single crystal positive electrode material is ≤0.03;
[0057] The lattice strain of the single crystal positive electrode material is ε, and ε is less than 0.2%.
[0058] The single crystal positive electrode material provided by the present application randomly selects 10 points of the single crystal positive electrode material for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the single crystal positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.03, indicating that the distribution uniformity of Ni, Co, and Mn elements inside the single crystal positive electrode material is good, which is conducive to reducing the crystal structure defects of the single crystal positive electrode material; the lattice strain ε of the single crystal positive electrode material is less than 0.2%, which can reduce the diffusion energy barrier of lithium ions between crystallites and increase the Li ion diffusion coefficient, so that the single crystal positive electrode material exhibits good rate performance and low DCR; at the same time, low lattice strain can also inhibit the generation of microcracks in the single crystal positive electrode material, thereby improving the cycle performance of the single crystal positive electrode material.
[0059] Specifically, the value of x can be 0.98, 0.99, 1.0, 1.01, 1.03, 1.05, 1.08, 1.09 or 1.1, etc., and is not limited here.
[0060] The specific value of a can be 0.50, 0.55, 0.60, 0.63, 0.70, 0.75, 0.80, 0.85, 0.88, 0.90, 0.95 or 0.98; the value of b can be 0.01, 0.05, 0.08, 0.10, 0.11, 0.13, 0.15, 0.18 or 0.20; the value of c can be 0.01, 0.05, 0.10, 0.15, 0.18, 0.20, 0.23, 0.27 or 0.30; the value of d can be 0, 0.01, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.10, etc., and is not limited here.
[0061] Specifically, the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material can be 0.01, 0.015, 0.02, 0.025, 0.026, 0.028 or 0.03, etc., which is not limited here.
[0062] In some embodiments, the range of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.08, and can be specifically 0.01, 0.02, 0.028, 0.03, 0.05, 0.057, 0.06, 0.07, 0.075 or 0.08, etc., and of course, it can also be other values within the above range, which are not limited here.
[0063] It can be understood that the lower the standard deviation and range of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material, the higher the uniformity of the distribution of Ni, Co and Mn elements in the single crystal positive electrode material. The standard deviation and range of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material in the present application are within the above range, indicating that the Ni, Co and Mn elements in the single crystal positive electrode material of the present application are evenly distributed, which is conducive to reducing the lattice defects of the single crystal positive electrode material, reducing the lattice stress, and improving the cycle performance and rate performance of the single crystal positive electrode material.
[0064] The lattice strain of the single crystal positive electrode material can specifically be 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.11%, 0.12%, 0.15%, 0.18% or 0.19%, etc., which is not limited here.
[0065] In some embodiments, the single crystal positive electrode material further includes a coating layer, the coating layer includes a metal oxide or a lithium ion conductor, wherein the metal in the metal oxide includes at least one of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co and Mn. The coating layer can reduce the direct contact between the single crystal positive electrode material and the electrolyte, reduce the occurrence of side reactions between the material and the electrolyte, and further improve the electrochemical performance of the single crystal positive electrode material.
[0066] In some embodiments, the grain size of the single crystal positive electrode material is D, 150nm<D<250nm. The grain size of the single crystal positive electrode material can specifically be 151nm, 155nm, 160nm, 170nm, 185nm, 190nm, 200nm, 205nm, 230nm or 245nm, etc., which is not limited here. If the grain size of the single crystal positive electrode material is less than 150nm, the cycle stability of the single crystal positive electrode material is poor; if the grain size of the single crystal positive electrode material is greater than 250nm, the capacity and rate performance of the single crystal positive electrode material are poor. Controlling the grain size of the single crystal positive electrode material within the above range is beneficial to improving the electrochemical performance of the single crystal positive electrode material.
[0067] It should be noted that the calculation method of grain size is generally calculated by using the half-width through the Scherrer formula. This method has a premise assumption, that is, the lattice stress is 0, and the broadening of the diffraction peak is entirely caused by the grain size. However, in fact, the lattice stress inside the single crystal positive electrode material cannot be completely ignored. Many factors cause stress concentration inside the single crystal positive electrode material. Therefore, the grain size calculated using the Scherrer formula has its inherent limitations. The present invention separates the diffraction peak broadening caused by the crystallite size and the diffraction peak broadening caused by the lattice stress through the Williamsone-Hall method, so the calculated grain size can better reflect the electrochemical properties of the material.
[0068] In some embodiments, the average particle size D of the single crystal positive electrode material is 50 The particle size of the single crystal positive electrode material is 1.5 μm to 5 μm, and specifically can be 1.5 μm, 1.8 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc. Of course, it can also be other values within the above range, which are not limited here. Controlling the particle size of the single crystal positive electrode material within the above range is beneficial to improving the structural stability, thermal stability and long cycle stability of the single crystal positive electrode material.
[0069] In some embodiments, the tap density of the single crystal positive electrode material is greater than 1.5 g / cm 3 , specifically 1.55g / cm 3 , 1.58g / cm 3 , 1.62g / cm 3 、1.63g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 or 1.75g / cm 3 When the tap density of the single crystal positive electrode material is controlled within the above range, it is beneficial to improve the energy density of the battery made of the single crystal positive electrode material.
[0070] In some embodiments, the compaction density of the single crystal positive electrode material is greater than 3.0 g / cm 3 , specifically 3.1 g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.5g / cm 3 、3.7g / cm 3 、3.9g / cm 3 or 4.1 g / cm 3 Of course, it can also be other values within the above range, which is not limited here.
[0071] In a second aspect, the present invention provides a positive electrode material precursor, the chemical formula of which is Ni a Co b Mn c N d O e , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y;
[0072] The surface area weighted average particle size D[3, 2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is less than or equal to 0.05.
[0073] In the prior art, during the reaction between the cathode material precursor and the lithium salt, the crystal growth rate of each micro-region inside the material is different due to the limitation of ion diffusion rate and temperature gradient, and the unit cell parameters are different, which will cause the accumulation of lattice stress inside the material; lattice stress will increase the diffusion energy barrier of Li ions between each crystal plane / grain boundary, reduce the Li ion diffusion coefficient, and finally increase the DCR of the material. The morphology and structural characteristics of the cathode material precursor have good inheritance for the cathode material, so the composition and structure of the cathode material precursor have a direct impact on the performance of the final cathode material. The positive electrode material precursor provided by the present application has a surface area weighted average particle size D[3, 2]<2.0μm, has high reaction activity, and is beneficial to improving the reaction efficiency and mass transfer efficiency in the subsequent preparation process of the positive electrode material from the positive electrode material precursor; at the same time, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor obtained by the above preparation method is ≤0.05, indicating that the distribution uniformity of Ni, Co and Mn elements in the positive electrode material precursor is good; using the positive electrode material precursor to prepare the positive electrode material can improve the distribution uniformity of Ni, Co and Mn elements in the positive electrode material, so that the positive electrode material prepared by the positive electrode material precursor has fewer crystal structure defects and smaller lattice stress.
[0074] In industry, the average particle size D is generally used. 50 To characterize the particle size of the cathode material precursor. However, the reaction between the cathode material precursor and the lithium salt is a process related to the contact area, so the Sauter average particle size, that is, the surface area weighted average particle size D[3,2] is actually more suitable for characterizing the particle size of the cathode material precursor. The larger D[3,2] is, the smaller the surface activity of the cathode material precursor is, and the slower the reaction rate with the lithium salt is.
[0075] It should be noted that the surface area weighted average particle size D[3,2] of the cathode material precursor in the present application can be directly measured by a Malvern 3000 laser particle size analyzer. Specifically, it can be obtained by the following formula: D[3,2]=(∑y 3 N d ) / (∑y 2 N d ) is calculated, where y is the particle size; N d is the number of particles with particle size y.
[0076] Specifically, the surface area weighted average particle size D[3,2] of the positive electrode material precursor can be 1.98 μm, 1.95 μm, 1.8 μm, 1.75 μm, 1.64 μm, 1.5 μm, 1.3 μm, 1.2 μm, 1.1 μm, 0.8 μm, 0.9 μm or 0.5 μm, etc., which is not limited here. When the surface area weighted average particle size D[3,2] of the positive electrode material precursor is controlled within the above range, the reaction activity of the positive electrode material precursor is high, which is beneficial to improving the reaction efficiency and mass transfer efficiency of the positive electrode material precursor in the subsequent sintering process with the lithium source.
[0077] The standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor can be 0.001, 0.005, 0.009, 0.01, 0.013, 0.02, 0.025, 0.03, 0.036, 0.04, 0.044, 0.045, 0.047 or 0.049, etc., which is not limited here.
[0078] In some embodiments, the range of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.12, and can be specifically 0.01, 0.015, 0.018, 0.02, 0.029, 0.03, 0.035, 0.048, 0.059, 0.06, 0.08, 0.097, 0.10, 0.105, 0.11, 0.112, 0.115 or 0.119, etc., and of course, it can also be other values within the above range, which are not limited here.
[0079] It can be understood that the standard deviation and range of the mass content of each element Ni, Co and Mn in the positive electrode material can reflect the uniformity of the distribution of Ni, Co and Mn elements in the positive electrode material precursor. The lower the standard deviation and range of the mass content of each element Ni, Co and Mn, the more uniform the distribution of Ni, Co and Mn elements in the positive electrode material precursor. At the same time, there is a good inheritance between the distribution uniformity of Ni, Co and Mn elements in the positive electrode material precursor and the distribution uniformity of Ni, Co and Mn elements in the single crystal positive electrode material. The more uniform the distribution of Ni, Co and Mn elements in the positive electrode material precursor, the more uniform the distribution of Ni, Co and Mn elements in the single crystal positive electrode material made from the positive electrode material precursor.
[0080] In the prior art, during the preparation of Ni / Co / Mn precursors, it is difficult to ensure that the environment for crystal nucleation and production in each microscopic region in the reactor is completely consistent, especially in continuous production. The concentrations of nickel, cobalt, manganese, and hydroxide ions in each region are difficult to be completely consistent, and local oversaturation is prone to occur. In addition, there is segregation during the Ni / Co / Mn precipitation process. This will cause uneven distribution of metal ion concentration in the precursor and poor stability. The defects in the precursor performance will also be transmitted to the positive electrode material accordingly, causing uneven distribution of metal ion concentration in the positive electrode material and defects in the crystal structure.
[0081] Therefore, controlling the standard deviation and range of the mass content of each element Ni, Co and Mn in the positive electrode material precursor within the above range is beneficial to improving the distribution uniformity of Ni, Co and Mn elements in the single crystal positive electrode material, so that the distribution uniformity of Ni, Co and Mn elements in the single crystal positive electrode material is good, the single crystal positive electrode material has fewer crystal structure defects and low lattice strain.
[0082] In some embodiments, the cathode material precursor includes secondary particles, and the secondary particles include a plurality of agglomerated primary particles.
[0083] In some embodiments, the cathode material precursor includes secondary particles, the secondary particles include a plurality of agglomerated primary particles, and the primary particles are spherical.
[0084] In some embodiments, the positive electrode material precursor includes secondary particles, and the secondary particles include a plurality of agglomerated primary particles, and the particle size of the primary particles is 20nm to 1000nm, specifically 20nm, 50nm, 80nm, 100nm, 150nm, 200nm, 500nm, 800nm or 1000nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. When the particle size of the primary particles is greater than 1000nm, the reaction activity on the surface of the positive electrode material precursor is poor, the lattice strain of the prepared single crystal positive electrode material is large, and the cycle performance and rate performance of the single crystal positive electrode material are poor. When the primary particles are less than 20nm, the tap density of the positive electrode material precursor is low, resulting in a low tap density of the prepared single crystal positive electrode material. Controlling the particle size of the primary particles within the above range is conducive to improving the cycle performance and rate performance of the single crystal positive electrode material made from the positive electrode material precursor.
[0085] In some embodiments, the average particle size D of the positive electrode material precursor is 50 <3.5 μm, specifically, it can be 0.5 μm, 0.8 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.2 μm or 3.5, etc., and of course, it can also be other values within the above range, which are not limited here. The particle size D of the positive electrode material precursor50 When controlled within the above range, it is beneficial to improve the reaction activity of the positive electrode material precursor.
[0086] In some embodiments, the specific surface area of the cathode material precursor is ≥5m 2 / g, specifically 5m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 50m 2 / g or 100m 2 / g, etc., and of course, other values within the above range may also be used, which are not limited here. The larger the specific surface area of the positive electrode material precursor, the higher the reactivity of the positive electrode material precursor, which is beneficial to the reaction between the lithium source and the positive electrode material precursor, and can reduce the lattice defects of the single crystal positive electrode material prepared from the positive electrode material precursor.
[0087] In some embodiments, the tap density of the cathode material precursor is greater than 1 g / cm 3 Specifically, it can be 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.8g / cm 3 , 2.3g / cm 3 , 2.5g / cm 3 or 3g / cm 3 When the tap density of the cathode material precursor is controlled within the above range, it is beneficial to improve the tap density of the prepared single crystal cathode material, thereby improving the energy density of the battery.
[0088] In a third aspect, the present application provides a method for preparing a single crystal positive electrode material, comprising the following steps:
[0089] Step S100, atomizing a mixed solution containing nickel salt, cobalt salt and manganese salt, and then thermally decomposing it to obtain a positive electrode material precursor, wherein the surface area weighted average particle size D[3,2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.05;
[0090] Step S200, after mixing the positive electrode material precursor with a lithium source, sintering in an oxygen-containing atmosphere to obtain a positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.03; the lattice strain of the single crystal positive electrode material is ε, and ε<0.2%.
[0091] The single crystal positive electrode material preparation method provided in the present application is to obtain a positive electrode material precursor by atomizing a mixed solution containing nickel salt, cobalt salt and manganese salt and then thermally decomposing it. The surface area weighted average particle size D[3,2] of the positive electrode material precursor is less than 2.0 μm, and the reaction activity is high, which is beneficial to improve the reaction efficiency and mass transfer efficiency of the positive electrode material precursor and the lithium source in the subsequent high-temperature sintering process; at the same time, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor obtained by the above preparation method is ≤0.05, indicating that the distribution uniformity of Ni, Co and Mn in the positive electrode material precursor is good; and then the single crystal positive electrode material prepared by the above positive electrode material precursor after subsequent sintering with the lithium source is The standard deviation of the mass content of the elements is ≤0.03, and the distribution uniformity of Ni, Co, and Mn elements inside the single crystal positive electrode material is good, which is conducive to reducing the crystal structure defects of the single crystal positive electrode material; and the lattice strain of the single crystal positive electrode material is low, and its lattice strain ε is less than 0.2%, which can reduce the diffusion energy barrier of lithium ions between crystallites and improve the Li ion diffusion coefficient, so that the single crystal positive electrode material exhibits good rate performance and low DCR; at the same time, low lattice strain can also inhibit the generation of microcracks in the single crystal positive electrode material, thereby improving the cycle performance of the single crystal positive electrode material.
[0092] Step S100, a mixed solution containing nickel salt, cobalt salt and manganese salt is atomized and then thermally decomposed to obtain a positive electrode material precursor, wherein the surface area weighted average particle size D[3, 2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.05.
[0093] Specifically, the surface area weighted average particle size D[3,2] of the positive electrode material precursor can be 1.98 μm, 1.95 μm, 1.8 μm, 1.75 μm, 1.64 μm, 1.5 μm, 1.3 μm, 1.2 μm, 1.1 μm, 0.8 μm, 0.9 μm or 0.5 μm, etc., which is not limited here. When the surface area weighted average particle size D[3,2] of the positive electrode material precursor is controlled within the above range, the reaction activity of the positive electrode material precursor is high, which is beneficial to improving the reaction efficiency and mass transfer efficiency of the positive electrode material precursor in the subsequent sintering process with the lithium source.
[0094] The standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor can be 0.001, 0.005, 0.009, 0.01, 0.013, 0.02, 0.025, 0.03, 0.036, 0.01, 0.044, 0.045, 0.047 or 0.049, etc., which is not limited here.
[0095] In some embodiments, the nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate.
[0096] In some embodiments, the cobalt salt includes at least one of cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt sulfate, cobalt nitrate, and cobalt acetate.
[0097] In some embodiments, the manganese salt includes at least one of manganese chloride, manganese carbonate, manganese sulfate, manganese oxalate, manganese nitrate, and manganese acetate.
[0098] In some embodiments, the molar ratio of Ni, Co and Mn in the mixed solution is (50-98): (0-20): (0-30), and the content of Co and Mn in the mixed solution is not 0. The molar ratio of Ni, Co and Mn in the mixed solution can be 50:0.1:0.1, 60:10:30, 65:15:20, 65:5:30, 70:5:25, 70:10:20, 80:5:15, 85:10:5 or 98:1:1, etc., which is not limited here.
[0099] In some embodiments, the total metal concentration in the mixed solution is 200 g / L to 500 g / L, specifically 200 g / L, 220 g / L, 260 g / L, 300 g / L, 350 g / L, 400 g / L, 450 g / L, 480 g / L or 500 g / L, etc. Of course, it can also be other values within the above range, which is not limited here.
[0100] In some embodiments, the mixed solution further includes a dopant containing an N element, wherein N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn, and Y.
[0101] In some embodiments, the chemical formula of the cathode material precursor is Ni a Co b Mn c N d O e, wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
[0102] In some embodiments, the range of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.12, and can be specifically 0.01, 0.015, 0.018, 0.02, 0.029, 0.03, 0.035, 0.048, 0.059, 0.06, 0.08, 0.097, 0.10, 0.105, 0.11, 0.112, 0.115 or 0.119, etc., and of course, it can also be other values within the above range, which are not limited here.
[0103] It can be understood that the standard deviation and range of the mass content of each element Ni, Co and Mn in the positive electrode material can reflect the uniformity of the distribution of Ni, Co and Mn elements in the positive electrode material precursor. The lower the standard deviation and range of the mass content of each element Ni, Co and Mn, the more uniform the distribution of Ni, Co and Mn elements in the positive electrode material precursor. At the same time, there is a good inheritance between the distribution uniformity of Ni, Co and Mn elements in the positive electrode material precursor and the distribution uniformity of Ni, Co and Mn elements in the single crystal positive electrode material. The more uniform the distribution of Ni, Co and Mn elements in the positive electrode material precursor, the more uniform the distribution of Ni, Co and Mn elements in the single crystal positive electrode material made from the positive electrode material precursor.
[0104] Controlling the standard deviation and range of the mass content of each element Ni, Co and Mn in the positive electrode material precursor within the above range is beneficial to improving the distribution uniformity of Ni, Co and Mn elements in the single crystal positive electrode material, so that the distribution uniformity of Ni, Co and Mn elements in the single crystal positive electrode material is good, the single crystal positive electrode material has fewer crystal structure defects and low lattice strain.
[0105] In some embodiments, the flow rate of the mixed solution is 100L / h to 900L / h, specifically 100L / h, 200L / h, 300L / h, 400L / h, 500L / h, 600L / h, 700L / h, 800L / h or 900L / h, etc., which are not limited here. When the flow rate of the mixed solution is controlled within the above range, the range and standard deviation of the mass content of each element of Ni, Co and Mn in the positive electrode material precursor are small, and the distribution uniformity of Ni, Co and Mn elements in the positive electrode material precursor is good.
[0106] In some embodiments, the pressure of the atomization treatment is 0.4 MPa to 0.8 MPa, specifically 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.75 MPa or 0.8 MPa, etc. Of course, it can also be other values within the above range, which is not limited here.
[0107] In some embodiments, the thermal decomposition temperature is 500°C to 850°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0108] Step S200, after mixing the positive electrode material precursor with a lithium source, sintering in an oxygen-containing atmosphere to obtain a positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.03; the lattice strain of the single crystal positive electrode material is ε, and ε<0.2%.
[0109] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.
[0110] In some embodiments, the molar ratio of lithium in the lithium source to the sum of nickel, cobalt and manganese in the positive electrode material precursor is 0.98-1.10, specifically 0.98, 0.99, 1.01, 1.03, 1.05, 1.06, 1.08, 1.09 or 1.10, etc., and of course it can also be other values within the above range, which is not limited here.
[0111] In some embodiments, the temperature of the sintering reaction is 750°C to 950°C, specifically 750°C, 760°C, 780°C, 800°C, 850°C, 900°C, 920°C or 950°C, etc. Of course, it can also be other values within the above range, which are not limited here. The sintering temperature is closely related to the Ni content. The higher the Ni content, the lower the sintering temperature. In addition, a suitable sintering temperature is conducive to reducing crystal structure defects and lattice strain, thereby improving the electrochemical performance of single crystal positive electrode materials.
[0112] In some embodiments, the sintering reaction time is 10 h to 30 h, specifically 10 h, 12 h, 15 h, 16 h, 18 h, 20 h, 24 h, 28 h or 30 h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0113] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises a positive electrode material prepared by the single crystal positive electrode material described in the first aspect or the single crystal positive electrode material preparation method described in the third aspect.
[0114] Example
[0115] Example 1
[0116] (1) Molar ratio (n) Ni :n Co :n Mn =0.67:0.05:0.28) nickel chloride, cobalt chloride and manganese chloride were weighed and added into water to prepare a mixed solution, and the total metal concentration in the mixed solution was controlled to be 300 g / L.
[0117] (2) After the mixed solution is atomized into droplets, it is placed in an air atmosphere in a roasting furnace for thermal decomposition at 650° C.; the flow rate of the mixed solution is controlled to be 200 L / h and the atomization pressure is controlled to be 0.6 MPa.
[0118] (3) The thermal decomposition product is subjected to air flow pulverization to obtain a positive electrode material precursor (Ni 0.67 Co 0.05 Mn 0.28 O).
[0119] (4) Molar ratio (n Ni+Co+Mn :n Li =1:1) The cathode material precursor was weighed and mixed with lithium carbonate, and then placed in an oxygen atmosphere and heated to 920° C. and sintered for 20 h to obtain a single crystal cathode material.
[0120] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D of the single crystal positive electrode material 50 The tap density is 3.8 μm and the tap density is 1.95 g / cm 3 .
[0121] Figure 1 This is a SEM morphology of the cathode material precursor prepared in Example 1 of the present application. Figure 2 Another SEM morphology of the cathode material precursor prepared in Example 1 of the present application is shown in FIG. Figure 1 and Figure 2 As shown, the positive electrode material precursor includes secondary particles, and the secondary particles include a plurality of agglomerated primary particles.
[0122] When observing the cathode material precursor prepared in Example 1 of the present application with a scanning electron microscope, 10 points of the cathode material precursor were randomly selected for EDS point scanning at a magnification of 3K to test the Ni, Co, and Mn contents. In the EDS spectrum results of the cathode material precursor, as shown in FIG. Figure 3 As shown, the range of Ni content in the positive electrode material precursor is 0.095, and the standard deviation is 0.036; the range of Co content is 0.029, and the standard deviation is 0.009; the range of Mn content is 0.081, and the standard deviation is 0.030. This shows that the positive electrode material precursor prepared in Example 1 has good distribution uniformity of Ni, Co, and Mn.
[0123] Figure 4 The Williamsone-Hall analysis fitting curve of the single crystal positive electrode material prepared in Example 1 of the present application is as follows: Figure 4 As shown, through Figure 4 By analyzing and calculating the data in, it can be obtained that the lattice strain of the single crystal positive electrode material is 0.11%.
[0124] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0125] Example 2
[0126] The difference from Example 1 is that (2) after the mixed solution is atomized into droplets, it is placed in an air atmosphere in a roasting furnace for thermal decomposition at 750°C; the flow rate of the mixed solution is controlled to be 200L / h and the atomization pressure is 0.6MPa.
[0127] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the single crystal positive electrode material is 3.7μm, and the tap density of the Baite is 1.85g / cm 3 .
[0128] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0129] Example 3
[0130] The difference from Example 1 is that (2) after the mixed solution is atomized into droplets, it is placed in an air atmosphere in a roasting furnace for thermal decomposition at 650° C.; the flow rate of the mixed solution is controlled to be 100 L / h and the atomization pressure is 0.6 MPa.
[0131] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28O2, the average particle size D50 of the single crystal positive electrode material is 4.0μm, and the tap density of the Baite is 2.12g / cm 3 .
[0132] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0133] Example 4
[0134] The difference from Example 1 is that (2) after the mixed solution is atomized into droplets, it is placed in an air atmosphere in a roasting furnace for thermal decomposition at 500°C; the flow rate of the mixed solution is controlled to be 500L / h and the atomization pressure is 0.6MPa.
[0135] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the single crystal positive electrode material is 3.8μm, and the tap density of the Baite is 1.90g / cm 3 .
[0136] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0137] Example 5
[0138] The difference from Example 1 is that (4) in molar ratio (n Ni+Co+Mn :n Li =1:1) The cathode material precursor was weighed and mixed with lithium carbonate, and then placed in an oxygen atmosphere and heated to 950° C. and sintered for 20 h to obtain a single crystal cathode material.
[0139] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the single crystal positive electrode material is 4.5μm, and the tap density of the Baite is 2.2g / cm 3 .
[0140] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0141] Example 6
[0142] The difference from Example 1 is that (4) in molar ratio (n Ni+Co+Mn :n Li =1:1) The cathode material precursor was weighed and mixed with lithium carbonate, and then placed in an oxygen atmosphere and heated to 900° C. for sintering for 20 h to obtain a single crystal cathode material.
[0143] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the single crystal positive electrode material is 3.0μm, and the tap density of the Baite is 1.68g / cm 3 .
[0144] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0145] Example 7
[0146] (1) Molar ratio (n) Ni :n Co :n Mn =0.88:0.06:0.04) nickel chloride, cobalt chloride and manganese chloride were weighed and added into water to prepare a mixed solution, and the total metal concentration in the mixed solution was controlled to be 300 g / L.
[0147] (2) After the mixed solution is atomized into droplets, it is placed in a calcining furnace under air atmosphere and thermally decomposed at 600° C.; the flow rate of the mixed solution is controlled to be 200 L / h and the atomization pressure is controlled to be 0.6 MPa.
[0148] (3) The thermal decomposition product is subjected to air flow pulverization to obtain a positive electrode material precursor (Ni 0.88 Co 0.06 Mn 0.04 O).
[0149] (4) Molar ratio (n Ni+Co+Mn :n Li =1:1) The cathode material precursor was weighed and mixed with lithium carbonate, and then placed in an oxygen atmosphere and heated to 850° C. and sintered for 15 h to obtain a single crystal cathode material.
[0150] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.88 Co 0.06 Mn 0.04 O2, the average particle size D50 of the single crystal positive electrode material is 3.2μm, and the tap density of the Baite is 1.77g / cm 3 .
[0151] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0152] Example 8
[0153] (1) Molar ratio (n) Ni :n Co :n Mn :n Al=0.88:0.06:0.03:0.03) nickel chloride, cobalt chloride, manganese chloride and aluminum chloride were weighed and added into water to prepare a mixed solution, and the total metal concentration in the mixed solution was controlled to be 300 g / L.
[0154] (2) After the mixed solution is atomized into droplets, it is placed in a calcining furnace under air atmosphere and thermally decomposed at 600° C.; the flow rate of the mixed solution is controlled to be 200 L / h and the atomization pressure is controlled to be 0.6 MPa.
[0155] (3) The thermal decomposition product is subjected to air flow pulverization to obtain a positive electrode material precursor (Ni 0.88 Co 0.06 Mn 0.03 Al 0.03 O).
[0156] (4) Molar ratio (n Ni+Co+Mn+Al :n Li =1:1) The cathode material precursor and lithium hydroxide were weighed and mixed evenly, and then placed in an oxygen atmosphere and heated to 850° C. and sintered for 15 h to obtain a cathode material.
[0157] The single crystal positive electrode material prepared in this embodiment has a general chemical formula of LiNi 0.88 Co 0.06 Mn 0.03 Al 0.03 O2, the average particle size D50 of the single crystal positive electrode material is 3.2μm, and the tap density of the Baite is 1.78g / cm 3 .
[0158] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0159] Comparative Example 1
[0160] The difference from Example 1 is that (2) after the mixed solution is atomized into droplets, it is placed in an air atmosphere in a roasting furnace for thermal decomposition at 880°C; the flow rate of the mixed solution is controlled to be 200L / h and the atomization pressure is 0.6MPa.
[0161] The single crystal positive electrode material prepared in this comparative example has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the positive electrode material is 3.82μm, and the tap density of the Baite is 1.86g / cm 3 .
[0162] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0163] Comparative Example 2
[0164] The difference from Example 1 is that (2) after the mixed solution is atomized into droplets, it is placed in an air atmosphere in a roasting furnace for thermal decomposition at 650°C; the flow rate of the mixed solution is controlled to be 1000L / h and the atomization pressure is 0.6MPa.
[0165] The single crystal positive electrode material prepared in this comparative example has a general chemical formula of LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the single crystal positive electrode material is 3.72μm, and the tap density is 1.90g / cm 3 .
[0166] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0167] Comparative Example 3
[0168] The difference from Example 1 is that (4) in molar ratio (n Ni+Co+Mn :n Li =1:1) The cathode material precursor and lithium carbonate were weighed and mixed evenly, and then placed in an oxygen atmosphere and heated to 700° C. and sintered for 20 h to obtain a cathode material.
[0169] The positive electrode material prepared in this comparative example is a polycrystalline positive electrode material, and its chemical formula is LiNi 0.67 Co 0.05 Mn 0.28 O2, the average particle size D50 of the polycrystalline positive electrode material is 3.2μm, and the tap density of the Baite is 1.8g / cm 3 .
[0170] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0171] Comparative Example 4
[0172] Preparation of Ni with reference to CN113488642A Example 2 0.88 Co 0.06 Mn 0.03 Al 0.03 (OH)2 quaternary precursor and corresponding positive electrode materials.
[0173] (1) preparing a first solution: nickel sulfate hexahydrate, manganese sulfate monohydrate, and cobalt sulfate heptahydrate were weighed according to a molar ratio of nickel:cobalt:manganese = 0.88:0.06:0.03, and dissolved in deionized water to prepare a transition metal salt solution with a mass concentration of 2 mol / L, referred to as the first solution;
[0174] (2) preparing the second solution: weigh aluminum nitrate nonahydrate and dissolve it in deionized water, then add concentrated ammonia water with a mass concentration of 25% dropwise to the aluminum salt solution while stirring continuously. When the pH value is 8-9, stop adding concentrated ammonia water, and finally adjust the volume to a concentration of aluminum hydroxide of 0.11 mol / L, which is called the second solution;
[0175] (3) Preparation of quaternary transition metal hydroxide precursor: Add ammonia water base liquid to the reactor in advance, control the temperature of the reaction system to 55°C, and adjust the stirring paddle speed to 1000rpm. Use metering pump No. 1 to add the first solution to the reactor at a rate of 35L / h, use metering pump No. 2 to add the second solution to the reactor at a rate of 20L / h, use metering pump No. 3 to add ammonia solution to keep the ammonia concentration in the system at 0.5mol / L, use metering pump No. 4 to add 4mol / L sodium hydroxide solution, and control the pH of the reaction system to 10.0±0.5. Continue to add materials for 17 hours, and after aging for 10 hours, filter and wash the final precipitated product, dry it in an oven at 110°C for 12 hours, and crush and sieve to obtain Ni 0.88 Co 0.06 Mn 0.03 Al 0.03 (OH)2 hydroxide precursor.
[0176] (4) The hydroxide precursor and lithium hydroxide were mixed evenly in a molar ratio of 1:1.05, sintered at 500°C for 3 h and 850°C for 15 h in an oxygen atmosphere, and after cooling, the product was crushed and sieved to a D50 of 12 μm to obtain a single crystal positive electrode material LiNi 0.88 Co 0.06 Mn 0.03 Al 0.03 O2.
[0177] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0178] Comparative Example 5
[0179] Reference CN116230922A to prepare Ni 0.8 Co 0.1 Mn 0.1 (OH)2 precursor and corresponding positive electrode materials.
[0180] (1) NiSO4, CoSO4 and MnSO4 were mixed in a Ni / Co / Mn molar ratio of 0.8:0.1:0.1 to prepare a solution.
[0181] (2) The solution was added into a reactor at 55° C., and NaOH and NH 3 ·H 2 O were used as precipitants and chelating agents for a co-precipitation reaction for 36 hours to obtain a Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 precursor.
[0182] (3) The precursor was dried at 80°C for 12 hours and then dried again at 110°C for 12 hours.
[0183] (4) Add the precursor and lithium hydroxide in a molar ratio of 1:1.05 into a dry high-speed mixer and mix for 5 minutes.
[0184] (5) The temperature was raised to 950°C at a rate of 2°C / min and maintained at 950°C for 5 hours, then naturally cooled to 900°C and maintained for 5 hours. During the heating and maintaining period, oxygen was continuously passed at a flow rate of 10 mL / min. After the calcination was completed, the mixture was naturally cooled to room temperature and crushed and classified to prepare LiNi 0.8 Co 0.1 Mn 0.1 Single crystal positive electrode material for O2.
[0185] Other performance parameters of the cathode material precursor and single crystal cathode material are shown in Table 1.
[0186] Test method:
[0187] (1) At a magnification of 3K, an energy dispersive X-ray spectrometer (EDS) attached to a scanning electron microscope is used to randomly select 10 points in the cathode material precursor or single crystal cathode material for scanning and testing the Ni, Co, and Mn contents of the cathode material precursor or single crystal cathode material. The standard deviation and range of the mass content of each element Ni, Co, and Mn are statistically analyzed to characterize the uniformity of the distribution of Ni, Co, and Mn elements.
[0188] (2) The surface area weighted average particle size D[3, 2] of the cathode material precursor was obtained by using a Malvern 3000 laser particle size analyzer.
[0189] (3) The lattice strain and grain size of the single crystal cathode material are calculated from the XRD data by Williamsone-Hall analysis:
[0190] The specific method is: using a Japanese Rigaku X-ray diffractometer to measure, the specific conditions are: 0.75 degrees / minute, step size 0.02, continuous scanning between 10 and 90 degrees in the 2θ range. hkl is the horizontal axis, β hkl cosθ hkl As the ordinate, the curve is drawn and linearly fitted. The strain ε and grain size D can be calculated by the slope and intercept. It is worth mentioning that the half-peak width β used in the fittinghkl It is necessary to eliminate the influence of the instrument, that is, β hkl =β 总 -β 仪器 , where β 总 is the half-peak width of the actual test, β 仪器 The half-peak width broadening caused by the instrument can be obtained by XRD calculation of the test standard silicon wafer. 仪器 In addition, the data of seven strong diffraction peaks (003), (101), (102), (104), (015), (107), and (113) were selected for fitting to improve the degree of linear fitting and reduce the actual test error.
[0191]
[0192] Where β is the half-peak width, θ is the diffraction angle, both in radians; k is a constant, which is 0.89; λ is the X-ray wavelength, which is 0.154nm; D is the grain size, in nm; ε is the lattice strain, which is dimensionless.
[0193] (4) Using a vibrator, weigh a certain amount of sample and vibrate 3000 times at 300 times / min to test the tap density.
[0194] (5) Electrochemical performance test:
[0195] The electrochemical performance of the material was evaluated using a button half-cell. The specific steps were as follows: single crystal positive electrode material, conductive carbon black, and PVDF were weighed in a mass ratio of 93:5:2, N-methyl-2-pyrrolidone (NMP) was added at a solid content of 50%, and a high-speed disperser was used to adjust the viscous slurry. The slurry was evenly coated on aluminum foil with a scraper, dried in an oven at 80°C, rolled, and cut into positive electrode sheets with a diameter of 14 mm. A 16 mm lithium sheet was used as the negative electrode sheet, a Celgard polypropylene film was used as the diaphragm, and a carbonate solution of LiPF6 with a concentration of 1 mol / L was used as the electrolyte. The assembly was performed in an argon-filled glove box to obtain a button half-cell. The capacity and cycle performance tests were performed at 25°C and 3.0-4.3V using the LAND battery test system, and the nominal capacity 1C was set to 200 mAh / g. In addition, the voltage UA at the beginning of each week’s discharge and the voltage data UB at the 60th second, the discharge current IDis, and the calculation formula of the DC internal resistance are DCR = (U A -U B ) / I Dis .
[0196] The above test results are detailed in Tables 1 and 2.
[0197] Table 1 Performance parameter results of positive electrode material precursors and single crystal positive electrode materials prepared in various embodiments and comparative examples
[0198]
[0199] Table 2 Electrochemical performance test results of single crystal positive electrode materials prepared in various embodiments and comparative examples
[0200]
[0201] According to the test data in Table 1 and Table 2, the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode materials prepared in Examples 1 to 8 is ≤0.03, and the range of the mass content of each element Ni, Co and Mn is ≤0.08, indicating that the distribution uniformity of Ni, Co and Mn elements inside the single crystal positive electrode material is good, which is conducive to reducing the crystal structure defects of the single crystal positive electrode material; the lattice strain ε of the single crystal positive electrode material is less than 0.2%, which can reduce the diffusion energy barrier of lithium ions between crystallites and increase the Li ion diffusion coefficient, so that the single crystal positive electrode material exhibits good rate performance and low DCR; at the same time, low lattice strain can also inhibit the generation of microcracks in the single crystal positive electrode material, thereby improving the cycle performance of the single crystal positive electrode material.
[0202] According to the data in Table 1, there is a good inheritance between the distribution uniformity of Ni, Co, and Mn elements in the cathode material precursor and the distribution uniformity of Ni, Co, and Mn elements in the single crystal cathode material. The smaller the range and standard deviation of the mass content of each element Ni, Co, and Mn in the cathode material precursor, the smaller the range and standard deviation of the mass content of each element Ni, Co, and Mn in the single crystal cathode material. In addition, the range and standard deviation of the Ni, Co, and Mn content in the single crystal cathode material are always smaller than those in the precursor. This is because high-temperature sintering is required in the preparation process of the single crystal cathode material, and the metal ions will further diffuse, thereby improving the distribution uniformity of the Ni, Co, and Mn elements.
[0203] According to the test data in Table 1 and Table 2, the single crystal positive electrode material prepared in Example 1 has the best comprehensive performance.
[0204] Comparing Example 1 and Example 2, the single crystal positive electrode material of Example 1 exhibits good rate performance, lower impedance, and higher cycle performance. This is because when the positive electrode material precursor is prepared in Example 1, the temperature of the atomized mixed solution for thermal decomposition is appropriate, so that the surface area weighted average particle size D[3,2] of the positive electrode material precursor is low, the positive electrode material precursor has high reactivity, the crystal structure defects of the single crystal positive electrode material are reduced, and the lattice strain of the single crystal positive electrode material is low. Therefore, the single crystal positive electrode material prepared in Example 1 exhibits better rate performance, lower impedance, and better cycle performance.
[0205] Compared with Example 1, in Example 5, during the sintering process of the cathode material precursor and the lithium source, the sintering temperature is increased, the range and standard deviation of the mass content of each element of Ni, Co and Mn in the single crystal cathode material are lower, and the lattice strain ε of the single crystal cathode material is reduced, so the cycle performance is improved. However, since the grain size of the single crystal cathode material is significantly larger and the Li ion diffusion path is longer, the rate performance of the single crystal cathode material prepared in Example 5 is lower than that in Example 1.
[0206] Compared with Example 1, in Example 6, during the sintering process of the positive electrode material precursor and the lithium source, the sintering temperature is reduced, which makes the grain size of the single crystal positive electrode material smaller and the lattice strain ε increases. Therefore, the cycle stability of the single crystal positive electrode material of Example 6 is lower than that of the single crystal positive electrode material of Example 1.
[0207] Compared with Example 1, Comparative Example 1 increases the thermal decomposition temperature of the positive electrode material precursor during the preparation process, so that the surface area weighted average particle size D[3, 2] of the positive electrode material precursor is greater than 2.0 μm; the positive electrode material precursor has poor reactivity, resulting in more defects in the subsequently prepared single crystal positive electrode material, and the lattice strain ε exceeds 0.2%, so that the single crystal positive electrode material exhibits poor rate performance, high DCR and low cycle performance.
[0208] Compared with Example 1, the atomization flow rate is increased during the preparation of the precursor of the positive electrode material of Comparative Example 2, and the standard deviation and variance of the mass content of each element Ni, Co and Mn in the prepared positive electrode material precursor are significantly increased, resulting in a decrease in the distribution uniformity of Ni, Co and Mn elements in the prepared single crystal positive electrode material, an increase in the lattice strain, and the lattice strain ε exceeds 0.2%. Therefore, the rate performance and cycle performance of the single crystal positive electrode material prepared in Comparative Example 2 are reduced.
[0209] Compared with Example 1, the sintering temperature of the positive electrode material in Comparative Example 3 is too low during the sintering of the precursor and the lithium source, and the obtained positive electrode material is a polycrystalline structure. The grain size of the positive electrode material is less than 150nm, and it has good rate performance; but the lattice strain exceeds 0.2%, and it is easy to crack and pulverize during the cycle process, which reduces the structural stability of the positive electrode material and causes a significant attenuation of the cycle capacity of the positive electrode material.
[0210] Compared with Example 1, the single crystal positive electrode material prepared in Comparative Example 4 has a surface area weighted average particle size D[3, 2] of the positive electrode material precursor that is too large, and the standard deviation and variance of the mass content of each element Ni, Co and Mn in the positive electrode material precursor are significantly greater than those in Example 1. Therefore, the lattice strain of the prepared single crystal positive electrode material is significantly increased, and the lattice strain exceeds 0.2%, resulting in a significant decrease in the rate performance and cycle performance of the single crystal positive electrode material.
[0211] Similarly, in the single crystal positive electrode material prepared in Comparative Example 5, the surface area weighted average particle size D[3, 2] of the positive electrode material precursor is too large, and the standard deviation and variance of the mass content of each element Ni, Co and Mn in the positive electrode material precursor are significantly greater than those in Example 1. Therefore, the lattice strain of the prepared single crystal positive electrode material is significantly increased, and the lattice strain exceeds 0.2%, which leads to a significant decrease in the rate performance and cycle performance of the positive electrode material.
[0212] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A single crystal positive electrode material, characterized in that: The chemical formula of the single crystal positive electrode material is Li x Ni a Co b Mn c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; When observing the single crystal positive electrode material with a scanning electron microscope, at a magnification of 3K, 10 points of the single crystal positive electrode material are randomly selected for EDS point scanning to test the Ni, Co, and Mn contents. In the EDS spectrum results of the single crystal positive electrode material, the standard deviation of the mass content of each element of Ni, Co, and Mn in the single crystal positive electrode material is ≤0.03; The lattice strain of the single crystal positive electrode material is ε, and 0.11%≤ε<0.2%.
2. The single crystal positive electrode material according to claim 1, characterized in that: The single crystal positive electrode material satisfies at least one of the following characteristics: (1) The grain size of the single crystal positive electrode material is D, 150nm<D<250nm; (2) The average particle size D of the single crystal positive electrode material 50 1.5μm~5μm; (3) The tap density of the single crystal positive electrode material is greater than 1.5 g / cm 3 ; (4) The maximum value of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.
08.
3. A positive electrode material precursor for preparing the single crystal positive electrode material according to any one of claims 1 to 2, characterized in that: The chemical formula of the positive electrode material precursor is Ni a Co b Mn c N d O e , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; The surface area weighted average particle size D[3, 2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is less than or equal to 0.
05.
4. The cathode material precursor according to claim 3, characterized in that: The positive electrode material precursor meets at least one of the following technical features: (1) The maximum value of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.12; (2) The positive electrode material precursor includes secondary particles, and the secondary particles include a plurality of agglomerated primary particles; (3) The positive electrode material precursor includes secondary particles, the secondary particles include a plurality of agglomerated primary particles, and the primary particles are spherical; (4) The positive electrode material precursor includes secondary particles, the secondary particles include a plurality of agglomerated primary particles, and the particle size of the primary particles is 20 nm to 1000 nm; (5) The average particle size D of the positive electrode material precursor 50 <3.5μm; (6) The specific surface area of the cathode material precursor is greater than 5 m 2 / g; (7) The tap density of the positive electrode material precursor is greater than 1 g / cm 3 .
5. A method for preparing a single crystal positive electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: A mixed solution containing nickel salt, cobalt salt and manganese salt is atomized and then thermally decomposed to obtain a positive electrode material precursor, wherein the surface area weighted average particle size D[3,2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.05; The positive electrode material precursor is mixed with a lithium source and then sintered in an oxygen-containing atmosphere to obtain a single crystal positive electrode material, wherein the standard deviation of the mass content of each element Ni, Co and Mn in the single crystal positive electrode material is ≤0.03; and the lattice strain of the single crystal positive electrode material is ε, and ε<0.2%.
6. The preparation method according to claim 5, characterized in that: The preparation method includes at least one of the following features: (1) The nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate and nickel acetate; (2) The cobalt salt includes at least one of cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt sulfate, cobalt nitrate and cobalt acetate; (3) the manganese salt comprises at least one of manganese chloride, manganese carbonate, manganese sulfate, manganese oxalate, manganese nitrate and manganese acetate; (4) The molar ratio of Ni, Co and Mn in the mixed solution is (50-98): (0-20): (0-30), and the content of Co and Mn in the mixed solution is not 0; (5) The total metal concentration in the mixed solution is 200 g / L to 500 g / L; (6) The mixed solution further includes a dopant containing an N element, wherein N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
7. The preparation method according to claim 6, characterized in that: The positive electrode material precursor includes at least one of the following features: (1) The chemical formula of the positive electrode material precursor is Ni a Co b Mn c N d O e , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; (2) The maximum value of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤ 0.12; (3) The surface area weighted average particle size D[3,2] of the positive electrode material precursor is less than 2.0 μm, and the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material precursor is ≤0.05; (4) The average particle size D of the positive electrode material precursor 50 <3.5μm; (5) The specific surface area of the cathode material precursor is greater than 5 m 2 / g; (6) The tap density of the cathode material precursor is > 1 g / cm 3 .
8. The preparation method according to claim 5, characterized in that: The preparation method includes at least one of the following features: (1) The flow rate of the mixed solution is 100 L / h to 900 L / h; (2) The pressure of the atomization treatment is 0.4MPa~0.8MPa; (3) The temperature of the thermal decomposition is 500°C to 850°C.
9. The preparation method according to claim 5, characterized in that: The preparation method includes at least one of the following features: (1) The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate; (2) The molar ratio of lithium in the lithium source to the sum of nickel, cobalt and manganese in the positive electrode material precursor is 0.98 to 1.10; (3) The sintering temperature is 750°C to 950°C; (4) The sintering time is 10h~30h.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the single crystal positive electrode material according to any one of claims 1 to 2 or the single crystal positive electrode material prepared by the method for preparing the single crystal positive electrode material according to any one of claims 5 to 9.
Citation Information
Patent Citations
Lithium ion quaternary positive electrode material, preparation method thereof and lithium ion battery
CN113488642A
Positive electrode active material for lithium secondary battery and lithium secondary battery comprising same
CN116230922A
Ternary positive electrode material and preparation method thereof
CN115626668A
Positive electrode active material, and lithium secondary battery
JP2010219065A
Positive electrode active material and preparation method therefor, positive electrode plate, lithium-ion secondary battery and battery module comprising same, battery pack, and device
WO2021042983A1
Cited By
Positive electrode material precursor, single crystal positive electrode material and preparation method therefor, and lithium-ion battery
EP4576259A1